Classroom Response System in a Super-Blended Learning and Teaching Model: Individual or Team-Based Learning? - Maryam Malekigorji; Taher Hatahet (MDPI AG, 2020)
Building an interactive environment during learning experience is sometimes hindered by student numbers in class, their sociocultural differences and limited teaching time, which may reduce student engagement. In this study we provided a super blended teaching and learning model by hybridising Classroom Response System (CRS) with Flipped Classroom (FC) and Team-Based Learning (TBL). CRS allowed learners to use their smart devices (e.g., phones, tablets and laptops) to respond to a variety of numerical, multiple-choice, short-answer and open ended questions posed during live classes and encouraged them to engage with classroom activities. Our Flipped-CRS (F-CRS) approach required the students to preview the e-learning material and watch the recorded lectures before the sessions and apply their knowledge within the session, either individually or as teams, by answering questions using TurningPoint CRS software. Learners provided positive feedback regarding F-CRS and the application of super blended teaching and learning model demonstrated a substantial increase in student collaboration and enhanced their motivation, engagement, attendance and academic performance, especially while using F-CRS approach in teams. Our super blended approach enabled educators to monitor student engagement throughout the year, facilitated formative assessment and assisted teachers to create crude class performance prediction in summative assessments.